FIND..................
Attachments:
![](https://hi-static.z-dn.net/files/d13/287130ffa97093aa719f48cdeac81718.jpg)
Answers
Answered by
2
To Integrate sin^3x cos^2x dx
=∫sinx (sin^2x)cos^2x dx
=∫sinx (1−cos^2x) cos^2xdx
=∫(sinx cos^2x−sinx cos^4x)dx
=−∫cos^2x(−sinx) dx+∫cos^4x(−sinx)dx
=−cos3x/3+cos5x/5+C
=1/15cos^3x(3cos^2x−5)+C
Please amrk as brainliest
Answered by
2
To Integrate sin^3x cos^2x dx
=∫sinx (sin^2x)cos^2x dx
=∫sinx (1−cos^2x) cos^2xdx
=∫(sinx cos^2x−sinx cos^4x)dx
=−∫cos^2x(−sinx) dx+∫cos^4x(−sinx)dx
=−cos3x/3+cos5x/5+C
=1/15cos^3x(3cos^2x−5)+C
Similar questions